Ambient temperature and prevalence of diabetes and insulin resistance in the Spanish population: Di@bet.es study. Issue 5 (May 2019) - Valdés, Sergio; Doulatram-Gamgaram, Viyey; Lago, Ana; García Torres, Francisca; Badía-Guillén, Rocío; Olveira, Gabriel; Goday, Albert; Calle-Pascual, Alfonso; Castaño, Luis; Castell, Conxa; Delgado, Elías; Menendez, Edelmiro; et al.
Abstract : Objective: The activity of brown adipose tissue is sensitive to changes in ambient temperature. A lower exposure to cold could result in an increased risk of developing diabetes at population level, although this factor has not yet been sufficiently studied. Design: We studied 5072 subjects, participants in a national, cross-sectional population-based study representative of the Spanish adult population (Di@bet.es study). All subjects underwent a clinical, demographic and lifestyle survey, a physical examination and blood sampling (75 g oral glucose tolerance test). Insulin resistance was estimated with the homeostasis model assessment (HOMA-IR). The mean annual temperature (°C) in each individual municipality was collected from the Spanish National Meteorology Agency. Results: Linear regression analysis showed a significant positive association between mean annual temperature and fasting plasma glucose ( β: 0.087, P < 0.001), 2 h plasma glucose ( β: 0.049, P = 0.008) and HOMA-IR ( β: 0.046, P = 0.008) in multivariate adjusted models. Logistic regression analyses controlled by multiple socio-demographic variables, lifestyle, adiposity (BMI) and geographical elevation showed increasing odds ratios for prediabetes (WHO 1999), ORs 1, 1.26 (0.95–1.66), 1.08 (0.81–1.44) and 1.37 (1.01–1.85) P for trend = 0.086, diabetes (WHO 1999) ORs 1, 1.05 (0.79–1.39), 1.20 (0.91–1.59) and 1.39 (1.02–1.90) P = 0.037, and insulin resistance (HOMA-IR ≥75th percentile of the non-diabetic population): ORs 1, 1.03 (0.82–1.30), 1.22 (0.96–1.55), 1.26 (0.98–1.63) ( P for trend = 0.046) as the mean annual temperature (into quartiles) rose. Conclusions: Our study reports an association between ambient temperature and the prevalence of dysglycemia and insulin resistance in Spanish adults, consistent with the hypothesis that a lower exposure to cold could be associated with a higher risk of metabolic derangements.